A Tumor‐Targeting Dual‐Stimuli‐Activatable Photodynamic Molecular Beacon for Precise Photodynamic Therapy. Issue 57 (22nd August 2022) - Tam, Leo K. B.; He, Lin; Ng, Dennis K. P.; Cheung, Peter C. K.; Lo, Pui‐Chi
Abstract: A multifunctional photodynamic molecular beacon (PMB) has been designed and synthesized which contains an epidermal growth factor receptor (EGFR)‐targeting cyclic peptide and a trimeric phthalocyanine skeleton in which the three zinc(II) phthalocyanine units are each substituted with a glutathione (GSH)‐responsive 2, 4‐dinitrobenzenesulfonate (DNBS) quencher and are linked via two cathepsin B‐cleavable GFLG peptide chains. This tailor‐made conjugate is fully quenched in the native form due to the photoinduced electron transfer effect of the DNBS moieties and the self‐quenching of the phthalocyanine units. It can target the EGFR overexpressed in cancer cells, and after receptor‐mediated endocytosis, it can be activated selectively by the co‐existence of intracellular GSH and cathepsin B, both of which are also overproduced in cancer cells, in terms of fluorescence emission and singlet oxygen generation. The cell‐selective behavior of this PMB has been demonstrated using a range of cancer cells with different expression levels of EGFR, while the stimuli‐responsive properties have been studied both in vitro and in various aqueous media. The overall results show that this advanced PMB, which exhibits several levels of control of the tumor specificity, is a promising photosensitizer for precise antitumoral photodynamic therapy. Abstract : A novel photodynamic molecular beacon has been designed and synthesized, which contains an epidermal growth factor receptor‐targeting cyclic peptide and a trimeric phthalocyanine skeleton which is activatable by the coexistence of glutathione and cathepsin B. It serves as a tumor‐targeting and dual‐stimuli‐responsive photosensitizer for precise photodynamic therapy.